Evaluation of the Various Clinical Presentations of Adult CNS Tuberculosis (Journal of Dhaka Medical College, 2020)
Background: Central nervous system (CNS) involvement is one of the most important extrapulmonary manifestations of tuberculosis (TB) causing considerable mortality and morbidity. Presentations of CNS TB are extremely variable. Treatments are generally more effective if the disease can be detected early. This study is to find out the various clinical patterns and investigation findings that might help in early detection of CNS TB.Objective: This study was conducted to detect various clinical manifestations of adult CNS TB at an earlier stage of evaluation.Methods: This was a hospital based observational study (cross sectional type) conducted on 30 patients of CNS TB who were admitted in Sir Salimullah Medical College Mitford Hospital, Dhaka during a period of 6 months from October 2013 to April 2014Results: Among the participants 53% were male and 47% were female, with a male female ratio of 1.13: 1. Mean age of the participants was 35.17±6.14 years. Tuberculosis involving brain (i.e. cranial TB) was most common (30.4%) in 15-24 years age group whereas spinal form of TB was most common (42.8%) in 25-34 years age group. Mean age of the participants having Brain TB was 36.46±6.90 years. Mean age of the participants having spinal TB was 32.36±12.52 years. Highest number of the cranial forms of TB was tuberculoma (52.2%) in this study and was found mostly in the young adults. Spinal TB was found in 25-34 years age group in highest number, all but one were Potts disease. Tuberculoma and tuberculous meningitis had an equal distribution in female sex while males had a higher (53.8%) occurrence of tuberculoma. On the other hand, spinal involvement was commoner in male sex (43.5%).Fever was the most common symptom noted in all forms of CNS TB patients (78.26% for brain and 71.43% for spinal cord TB patients) followed by headache and loss of consciousness representing 2nd and 3rd common symptom in brain TB patients. Most common clinical signs in brain TB were signs of meningeal irritation (65.22%), cranial nerve palsies and papillodema while spastic paraparesis with sensory level being the commonest in spinal cases. Tuberculoma was the most frequent neuro-radiologic findinds in case of brain TB patients and paraspinal soft tissue shadow with vertebral collapse was commoner in spinal TB patients.Conclusion: This study has highlighted the relative frequency of various types of brain and spinal TB lesions along with the symptoms, signs and laboratory findings in Bangladeshi adult patients. In Bangladesh, tuberculosis should be always an important differential diagnosis in patients of fever with headache as well as spastic paraplegia or quadriplegia for any duration in any sex group.J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 76-84